2017
DOI: 10.1123/mc.2015-0097
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Linear and Nonlinear Parameters in the Swim Strokes According to the Level of Expertise

Abstract: The aim was to examine the variation of linear and nonlinear proprieties of the behavior in participants with different levels of swimming expertise among the four swim strokes. Seventy-five swimmers were split into three groups (highly qualified experts, experts and nonexperts) and performed a maximal 25m trial for each of the four competitive swim strokes. A speed-meter cable was attached to the swimmer's hip to measure hip speed; from which speed fluctuation (dv), approximate entropy (ApEn) and fractal dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 23 publications
3
31
0
Order By: Relevance
“…Only a couple of papers have reported yet the FD in human swimming. Barbosa et al [6] noted a FD of 1.84 ± 0.08, 1.85 ± 0.09 and 1.89 ± 0.06 at front-crawl for highly-qualified, expert and non-expert swimmers, respectively. In this paper it was concluded that the level of expertise will affect the complexity of the motor system.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Only a couple of papers have reported yet the FD in human swimming. Barbosa et al [6] noted a FD of 1.84 ± 0.08, 1.85 ± 0.09 and 1.89 ± 0.06 at front-crawl for highly-qualified, expert and non-expert swimmers, respectively. In this paper it was concluded that the level of expertise will affect the complexity of the motor system.…”
Section: Discussionmentioning
confidence: 98%
“…A very recent paper compared the level of complexity of swimming according to level of expertise. It was noted that swimming does exhibit nonlinear properties but its magnitude differs according to the swim stroke and level of expertise of the performer [6]. The FD was higher with large effect sizes in the group of non-experts than in high-tier swimmers (highlyqualified and expert cohort groups).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previously observed differences in IVV (Barbosa, Goh, Morais, & Costa, 2016;Matsuda et al, 2014;Schnitzler et al, 2010), we hypothesised that the elite swimmers would swim more smoothly than the non-elite swimmers, and thus have a lower jerk cost. We further hypothesised that within a group of (elite or non-elite) swimmers the faster swimmers would show more jerk than the slower swimmers because swimming faster is associated with greater accelerations and decelerations (Leblanc, Seifert, Tourny-Chollet, & Chollet, 2007) and thus greater jerk.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of the swimming technique also varies depending on the level of expertise. The dv, ApEn and FD decreases with increasing expertise (frontcrawl: 15.11 ≤ dv ≤ 18.40; 0.66 ≤ ApEn ≤ 0.73; 1.84 ≤ FD ≤ 1.89) (Barbosa, Goh, Morais, & Costa, 2017). These two papers only assessed the variations of nonlinear characteristics depending on the swim stroke performed (task constraint) and the competitive level (organismic constraint) of the performer.…”
Section: Introductionmentioning
confidence: 99%